Inventário de fungos gasteroides (Agaricomycetes, Basidiomycota) em uma área de transição entre Cerrado e Mata Atlântica no Sudoeste de São Paulo - Fernandes, Natiele Stephanie Rubio (Universidade Federal de São Carlos, 2019)
Gasteroid fungi comprise a group of fungi belonging to the class Agaricomycetes. Gasteromycetes are characterized by basidiospores that remain closed within the basidioma until complete maturation, requiring some mechanical stimulation or external agents for their release, an exclusive characteristic of the group. They present several strategies for spore dispersion, and wide applicability, where besides the ecological importance, performed as decomposers, denotes potential for application in several areas such as: forestry, agriculture, food, etc.There are a considerable number of ectomycorrhizal species, which have established relationships with roots of various plant species. Considering the importance of the group and the scarcity of studies, more studies are necessary to better understand the diversity and taxonomy of the group. This project aimed to survey gasteroid fungal species in the municipality of Buri, South western São Paulo. In this area, the main phytophysiognomies represented are Atlantic Forest (Dense Ombrophilous Forest and Mixed Ombrophilous Forest or Araucaria Forest) with Cerrado patches. Basidiomes were collected for identification between August 2017 and August 2019. After collection, the basidiomes were subsequently dehydrated and examined with stereoscopic microscope and light microscope. The identification of the examples was performed with the help of specialized literature and comparison with herbarium samples. The specimens were deposited in the SPSC herbarium. In total, 33 specimens were gathered, which represent 15 taxa distributed in 7 genera, belonging to 5 families: Agaricaceae Chevall. (Calvatia Fr., Lycoperdon P. Micheli), Geastraceae Corda (Geastrum Pers.), Nidulariaceae Dumort. (Cyathus Haller), Phallaceae Corda (Abrachium Baseia & T.S. Cabral, Clathrus P. Micheli ex L., Phallus Juniusex L.) e Sclerodermataceae Corda (Scleroderma Pers., Pisolithus Alb. & Schwein.). The families Geastraceae and Phallaceae were the most representative, and the families Agaricaceae, Nidulariaceae and Sclerodermataceae were the least represented. In this survey, Cyathus julietae and Phallus rubicundus were the taxa with the largest number of collected specimens. Another relevant result was color of the volva of P. rubicundus (a species reported from the state of São Paulo after three decades), reporting that it may have a purplish coloration, differing from literature which describes exclusively white volva for the species. From this observation it is possible to discuss the validation of features to circumscribe Phallus species, since some members in the genus are separated solely based on the volva pigmentation. The present study also contributes with four new reports from the state of São Paulo: Geastrum javanicum Lév., Geastrum minimum Schwein., Cyathus julietae H.J. Brodiee, and Scleroderma areolatum Ehrenb., thus increasing the knowledge about gasteroid mycota in Brazil.
Inventory of gasteroid fungi (Agaricomycetes, Basidiomycota) in a transition area between Cerrado and Atlantic Forest in Southwestern São Paulo
Keywords: Gasteromicetos; Micota; Taxonomia de fungos; Gasteromycetes; Mycota; Fungal taxonomy; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS BIOLOGICAS::MORFOLOGIA; CIENCIAS BIOLOGICAS